1977
DOI: 10.1037/0022-006x.45.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Students play therapist: Relative effects of role playing, videotape feedback, and modeling in a simulated interview.

Abstract: Assessed role playing, videotape feedback, and modeling in combination, using 18 male and 30 female undergraduates randomly allocated into 4 groups of 12 Ss each: no-treatment controls, role playing, video feedback, and modeling. The control condition consisted of a waiting period, and the other 3 groups "played therapist" for 2 12-min sessions with a "client" confederate. Interposed between Sessions 1 and 2 was a 12-min interval during which the role-playing group merely waited, the feedback group received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
3

Year Published

1979
1979
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 16 publications
(21 reference statements)
1
29
0
3
Order By: Relevance
“…From these data, it seems that beneficial effects cannot always be presumed when role-play practice is added to some other training component. These findings, when considered along with ones reported by Bailey et al (1977), O'Toole (1979), and Stone (1975), point to role-play practice as a potentially facilitative treatment that needs further investigation if it is to yield the results anticipated by its many participants and by the professionals who routinely use it in training.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…From these data, it seems that beneficial effects cannot always be presumed when role-play practice is added to some other training component. These findings, when considered along with ones reported by Bailey et al (1977), O'Toole (1979), and Stone (1975), point to role-play practice as a potentially facilitative treatment that needs further investigation if it is to yield the results anticipated by its many participants and by the professionals who routinely use it in training.…”
Section: Discussionmentioning
confidence: 65%
“…While this study and the studies reported by Bailey et al (1977) and O'Toole (1979) looked at role-play practice in the context of training novice counselors in rudimentary clinical interviewing skills, the implications for practice and for further research can and probably should be extended to other learning environments where role-play practice is introduced singly or in combination with another training component. The fact is that role-playing is a commonly used and well-received training activity in a variety of learning environments, and, although we seem to know very little about the conditions that control its effectiveness, it continues to be used without question.…”
Section: Implications For Practice and For Future Researchmentioning
confidence: 95%
See 1 more Smart Citation
“…Alexander & Scriven, 1977;Bailey, Deardorff & Nay, 1977;Heller, Myers & Kline, 1963;Whiteley & Jakubowski, 1969). Although there have been criticisms of the inter-interview consistency of the coached client's presentation, Whiteley and Jakubowski (1969) showed that having the coached client make a list of 16 content-relevant statements and include these in interviews dramatically improved this consistency.…”
Section: Introductionmentioning
confidence: 99%
“…Use of observational learning, a basic component of social learning theory, is well-documented in the literature (e.g., Bailey, Deardorff, & Nay, 1977;Fridman & Stone, 1978;Gulanick & Schmeck, 1977;OToole, 1979; Dalton & Sundblad, 1976; Robinson, Froehle, & Kurpius, 1979a). There has been little research however, on how models can best be presented to enhance learning.…”
mentioning
confidence: 99%